Effects of the COVID-19 Pandemic on Patients with Tuberculosis - Gokceoglu, Sonay; Beyaz, Emine (Erciyes Univ Sch Medicine, 2024)
Objective: People with tuberculosis (TB) are highly vulnerable to the coronavirus pandemic due to pre-existing lung damage, leading to a higher risk of complications from Coronavirus Disease 2019 (COVID-19). This study aims to examine the effects of the COVID-19 pandemic on patients with tuberculosis. Materials and Methods: A descriptive study was conducted with 101 TB patients between January and October 2021. Data analysis was performed using descriptive statistics (numbers, percentages), Fisher's Exact Test, Pearson's Chi -Squared Test, and multiple logistic regression. Results: Among the TB patients, 42.6% were negatively affected during the pandemic, while 57.4% were not affected. A total of 43.6% of patients received all COVID-19 vaccines. Factors including education level above primary school (65.9%), income level equal to or higher than expenses (71.4%), mask usage (61.5%), and a history of relapse or returning from treatment (100.0%) were significantly impacted by the pandemic. Logistic regression analysis revealed that mask usage increased the likelihood of being adversely affected by 3.0 times, while having an income equal to or greater than expenditures increased it by 4.5 times (p<0.05). Conclusion: With the positive influence of education, the demand for hospital and health services access increased among tuberculosis patients who experienced an improvement in their economic situation. However, even those who regularly used masks made mistakes in their usage. Consequently, these groups have been adversely affected during the COVID-19 pandemic.
Keywords: COVID-19; epidemiology; health care; pandemics; tuberculosis